Tegangan antara Percepatan Target dan Kepastian Hukum: Analisis Yuridis Validitas Alat Bukti dalam Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Desa Ciparay - Sri Wulan Dewi; Dedy Hernawan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study is grounded in the tension between two competing interests in the implementation of the Comprehensive Systematic Land Registration Programme (PTSL): the pressure to meet quantitative administrative targets set by the government and the need to safeguard the juridical validity of land ownership evidence as the basis for legal certainty. This study aims to examine the extent to which the acceleration of PTSL target achievement in Ciparay Village potentially affects the thoroughness of juridical evidence verification and to analyse the legal risk-mitigation measures undertaken by the implementing committee. The method employed was an empirical legal approach with a descriptive-analytical focus. Primary data were obtained through interviews with the National Land Agency (BPN) of Bandung Regency, the PTSL committee and the Ciparay Village administration, as well as questionnaires distributed to 70 community members who received PTSL certificates. Secondary data were obtained through a literature review of legislation, journals and other supporting documents. The findings show that PTSL realisation in Ciparay Village reached 512 land parcels, or 102.4% of the 500-parcel quota, with 505 certificates (98.63%) handed over, while 5 certificates (0.98%) remained undelivered, 1 file (0.20%) was returned for correction and 1 application (0.20%) was cancelled. This study finds that target pressure gave rise to a tiered application of the good-faith principle, whereby dryland parcels whose physical possession was easily evidenced through witness testimony were prioritised, while rice-field parcels were processed last due to their susceptibility to unilateral claims by cultivators and the scarcity of written evidence. This practice reveals a gap between the normatively required “clear and clean” principle and the practical limits of juridical proof in the field, which may give rise to legal uncertainty in the future despite the administrative target having been exceeded. Accordingly, the quantitative success of PTSL in Ciparay Village must be read critically through the lens of legal certainty, rather than merely as an administrative achievement.